2006
DOI: 10.1002/nbm.1023
|View full text |Cite
|
Sign up to set email alerts
|

Magnetisation transfer ratio of choline is reduced following epileptic seizures

Abstract: The purpose of this study was to characterise the concentration and magnetisation transfer ratio (MTR) of brain metabolites following epileptic seizures. Magnetic resonance spectroscopy was performed in 10 patients with temporal or extra-temporal lobe epilepsy as soon as possible after a seizure, with a second interictal scan between 1 and 3 days after the postictal scan and 10 healthy controls were scanned twice. Voxels (26 +/- 2 mL) were placed in the frontal lobe in all patients and controls, on the side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Although these studies found both elevated and reduced mI concentrations , there are explanations for the contradictory results. Diminished mI has been reported in medicated patients with, for example, valproate and carbamazepine, and elevated mI has been found in unmedicated patients, suggesting that patients may have elevated pretreatment mI . In addition, an animal study showed that antiepileptic medication (valproate) decreases mI concentration in rat brains .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies found both elevated and reduced mI concentrations , there are explanations for the contradictory results. Diminished mI has been reported in medicated patients with, for example, valproate and carbamazepine, and elevated mI has been found in unmedicated patients, suggesting that patients may have elevated pretreatment mI . In addition, an animal study showed that antiepileptic medication (valproate) decreases mI concentration in rat brains .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, abnormal mI concentrations were found in different forms of epilepsy and in patients with autism spectrum disorders . Furthermore, studies have shown that antiepileptic medication has an influence on inositol biosynthesis and mI metabolism in patients with epilepsy , and SCN1A polymorphism has an influence on the medication doses used in this disease . This suggests a direct link between SCN1A and mI concentration.…”
Section: Introductionmentioning
confidence: 99%
“…For patient studies, single voxels should yield more reliable results. For example, we recently demonstrated a significant reduction in the MTR of Cho following epileptic seizures using such a single‐voxel approach (21).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the literature has usually suggested 1 H-MRS as a supplementary tool in the interictal localization of seizure foci. In six studies the possible role of this modality was studied in the ictal and postictal phases [42][43][44][45][46][47]. F. Fadaie et al showed significant decreases in the NAA/Cr, NAA/Cho, and NAA/Cr+Cho ratios immediately after ictus in the ipsilateral hippocampus compared with the contralateral hippocampus of patients and controls.…”
Section: Methodological Review Of Hippocampal 1 H-mrs Studies In Tlementioning
confidence: 99%